Postmortem Diagnosis of Gastric Ulcer Perforation and Peritonitis with Sarcina Ventriculi: A Case Report: Sarcina Ventriculi Infection - Buğra, Aytül; Daş, Taner; Elgörmüş, Neval; Ayaz, Gizem (The Bulletin of Legal Medicine, 2019)
Sarcina ventriculi is a gram-positive anaerobic coccus with characteristic tetrad morphology. Sarcina ventriculiis identified by light microscopy with features of basophilic staining, cuboidal shape, tetrad morphology, and refractile nature. There have been very few case reports of Sarcina ventriculi reported in the literature. We present a case of a 53-year-old male, with gastric ulcer perforation where peritonitis was incidentally found to harbor Sarcina ventriculi in postmortem histopathological examination. Most of the cases exhibit abdominal pain, nausea, vomiting and delayed gastric emptying. It has also fatal life-threatening complications, such as gastric perforation and emphysematous gastritis. The histopathological examination has a key role for identification of the bacteria. The pathologist must always keep it in mind these bacteria as a cause of gastric ulcer perforation in the differential diagnosis. We want to present a case of a 53-year-old male gastric ulcer perforation who was found dead in his bed.